Factors that influence IT students’ cyberchondria: Perspectives from the Philippines - Bonus, Don Erick (Animo Repository, 2021)
Strides in bridging the digital divide along with wider affordable Internet ushered in a society that is highly dependent on online information. Diverse users with varying interests have used the Internet as a source of information to fulfill their needs such as individuals in the technology, healthcare and government sectors. While these benefits have been widely applauded, this thirst for knowledge online led to the birth of a problem called cyberchondria or the excessive search for medical information that may cause negative effects on an individual’s well-being. Information Technology students have been found to demonstrate a high level of computer self-efficacy allowing them to search for medical information online with ease making them more susceptible to cyberchondria. We approached 187 university students enrolled in an Information Technology program to answer a validated scale incorporating factors that have been found to be strong determinants of cyberchondria. Results were analyzed using PLS-SEM and we found that a high degree of neuroticism and computer self-efficacy can lead to cyberchondria. While a low level of self-esteem, has a positive influence on cyberchondria, this cannot be supported at a significant level. Finally, interventions and literacy programs would be valuable preventive systems in curbing the harmful effects of cyberchondria.